2016
DOI: 10.1371/journal.pone.0154022
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Trafficking, Engraftment, and Delivery of Nanoparticles and an Exogenous Gene into the Acutely Inflamed Brain Tissue – Evaluations on Monocyte-Based Delivery System for the Central Nervous System

Abstract: The ability of monocytes and monocyte-derived macrophages (MDM) to travel towards chemotactic gradient, traverse tissue barriers, and accumulate precisely at diseased sites makes them attractive candidates as drug carriers and therapeutic gene delivery vehicles targeting the brain, where treatments are often hampered by the blockade of the blood brain barrier (BBB). This study was designed to fully establish an optimized cell-based delivery system using monocytes and MDM, by evaluating their homing efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The BBB is notoriously difficult to cross; the microvascular endothelial cells that form the neurovascular unit are characterized by several restrictive features, including the expression of tight junction complexes, a lack of fenestrations, and low pinocytic activity . As a result, there has been significant research into methods for improving nanoparticle transport through the BBB, using ideas ranging from physically disrupting the endothelium using ultrasound combined with microbubbles, to coating nanoparticles with ligands that enhance transcytosis, to using live cells as delivery vehicles . While there has been some investigation into how nanoparticle properties modulate transport into the brain, overall very little is known about how these differences affect their biological performance.…”
Section: Introductionmentioning
confidence: 99%
“…The BBB is notoriously difficult to cross; the microvascular endothelial cells that form the neurovascular unit are characterized by several restrictive features, including the expression of tight junction complexes, a lack of fenestrations, and low pinocytic activity . As a result, there has been significant research into methods for improving nanoparticle transport through the BBB, using ideas ranging from physically disrupting the endothelium using ultrasound combined with microbubbles, to coating nanoparticles with ligands that enhance transcytosis, to using live cells as delivery vehicles . While there has been some investigation into how nanoparticle properties modulate transport into the brain, overall very little is known about how these differences affect their biological performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we showed that some homing genes were downregulated by Dex microparticle treatment while others were upregulated, but these results are likely confounded by the fact that we analyzed the cells after their differentiation into macrophages, which is known to inhibit homing capacity relative to monocytes 62 .…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, we chose dexamethasone for proof of concept, but a drug that promotes a more regenerative macrophage phenotype would be a better choice for studying therapeutic efficacy. Finally, within this paper we have not characterized the effect of microparticle-loading on the homing capacity of monocytes, although other groups have completed similar characterizations 52,53,62 , but this will be important if monocytes are to be administered systemically.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows good permeation behavior. 25,26 Some other similar studies also demonstrated the application of monocytes for drug cargo to the brain. Although, cell-mediated transport has major disadvantages like early release of the freight, failure to reach the particular site of action and poor drug loading ability.…”
Section: Adsorptive Mediated Transcytosis (Amt)mentioning
confidence: 86%